Peningkatan Pengetahuan Keluarga Petani melalui Edukasi Gizi Seimbang untuk Mendukung Pencegahan Stunting - Sarman; Hairil Akbar; Fachry Rumaf; Moh. Rizki Fauzan; Saharuddin; Taza Valensia Mokodompit; Putri Ersa Potabuga; Qendy Aulia Lantong (STIKES Yayasan RS.Dr.Soetomo, 2026)
Stunting remains a major public health challenge in developing nations like Indonesia, heavily influenced by family knowledge regarding child nutrition. The objective of this community service initiative was to improve the knowledge of farming families regarding balanced nutrition as an effort to prevent stunting in Abak Village. The methods used were a participatory-educational approach involving 80 participants, primarily farming families with pregnant women and/or toddlers. The intervention consisted of interactive lectures, group discussions, and simple demonstrations of balanced menus using local food sources. Pre-tests and post-tests were administered to evaluate changes in participant knowledge. The baseline data revealed limited initial understanding, with an average pre-test knowledge score of only 36%. Following the educational intervention, the average knowledge score significantly increased to 88%, reflecting a substantial improvement of 52%. The highest increase was observed in understanding the importance of routine child growth monitoring, which rose by 55%. Family-based nutritional education is highly effective in improving community literacy and knowledge regarding stunting prevention. Continuous mentoring and active involvement of health volunteers are recommended to sustain long-term behavioral changes.